O papel da administradora de consórcios e do Bacen, à luz da Lei nº 11.795/2008 e do Código de Defesa do Consumidor - Almeida, Jesus Cláudio Pereira de (2011)
This paper has as its objective to analyze the role of the consortium agency as well as of BACEN (Central bank of Brazil), having as its base the Consortium Law Law nº 11.795, from October, 8th, 2008 and the rules of the Uniform Commercial Code which is, at the same time, the main topic and main goal of such dissertation. In order to handle this analysis, it was used, as methodological support, the exploratory research with deductive and investigative approach; also, the bibliography research technique was used, with a theory reference based on secondary sources, especially the doctrine and jurisprudence are taken into consideration. As the organization is concerned, the paper is divided in six chapters, which are considered essential to cover the theme proposed herein. Thus, in the first chapter, the system of consortiums to acquire assets and services is discussed. The second is dedicated to the study of the principle sustaining the consume relations under the Federal Constitution, also mentioning the Consumer Code. In the sequence, the third chapter guides us to the definition, principles and peculiarities of Consumer s contracts, ending with the standard contracts analysis and the general contractual clauses. The fourth and fifth chapters talk about the contract and the contract of consortiums in relation to the UCC. The sixth and last chapters explore, inside the scope of the research, the role of the agency of consortiums and the Central Bank in Brazil when faced with the disciplinary measures of the Consortium Law and the UCC. From the study, it is possible to conclude that even though there is uncertainty concerning the jurisprudence, specifically as the administrative fee charges are concerned, the new legislation has brought harmony for the interested parties, strengthening the balance between the contract and its social function, with benefits for the civil society and specially in the sake of the consumer